2020
DOI: 10.1167/iovs.61.10.51
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Method of Visual Field Sensitivity Using Fundus Autofluorescence Images in Patients With Retinitis Pigmentosa

Abstract: The purpose of this study was to investigate the association between fundus autofluorescence (FAF) and visual field (VF) sensitivities in eyes with retinitis pigmentosa (RP). We also investigated the model we developed to predict VF sensitivity using the FAF ring and its prediction accuracy. METHODS. The training dataset consisted of 51 eyes of 28 patients, and the testing dataset consisted of 42 eyes of 25 patients with RP. VF and FAF measurements were conducted using the Humphrey Field Analyzer (HFA) 10-2 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…35 In contrast, we recently showed that the structural damage in RP, such as fundus auto uorescence, was more accurately measured by VF sensitivity 34,35 using the HFA 10 − 2 test. 36 The current results will be useful when assessing the effects of any candidate treatment on the progression of VF with the HFA 10 − 2 test. In addition, as suggested in a previous study, visual disability is closely associated with HFA 10 − 2 test results, 5 and the current results will be useful when predicting patients' future daily lives using the HFA 10 − 2 test.…”
Section: Discussionmentioning
confidence: 97%
“…35 In contrast, we recently showed that the structural damage in RP, such as fundus auto uorescence, was more accurately measured by VF sensitivity 34,35 using the HFA 10 − 2 test. 36 The current results will be useful when assessing the effects of any candidate treatment on the progression of VF with the HFA 10 − 2 test. In addition, as suggested in a previous study, visual disability is closely associated with HFA 10 − 2 test results, 5 and the current results will be useful when predicting patients' future daily lives using the HFA 10 − 2 test.…”
Section: Discussionmentioning
confidence: 97%
“… 42 For instance, we previously developed a model to predict VF sensitivity measured with the HFA 10-2 test using visual acuity in RP. 19 The study revealed that the model improved when the assessment of the structural damage demonstrated with fundus autofluorescence imaging was combined, implying the limitation of using visual acuity in establishing the severity of disease in RP. The current results suggest that the binomial PLR method will be useful in assessing VF progression with the HFA 10-2 test when evaluating the effects of any candidate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One example of this effort is a model to predict the central VF sensitivity from the structural damage demonstrated by fundus autofluorescence imaging in RP. 19 In the current study, we investigated whether binomial PLR is useful in evaluating VF progression in the central 10°, in eyes with RP.…”
Section: Introductionmentioning
confidence: 99%
“…35 In contrast, we recently showed that the structural damage in RP, such as fundus autofluorescence, was more accurately measured by VF sensitivity 34 35 using the HFA 10-2 test. 36 The current results will be useful when assessing the effects of any candidate treatment on the progression of VF with the HFA 10-2 test. In addition, as suggested in a previous study, visual disability is closely associated with HFA 10-2 test results, 5 and the current results will be useful when predicting patients' future daily lives using the HFA 10-2 test.…”
Section: Open Accessmentioning
confidence: 98%